Formulation and Evaluation of Tamoxifen Citrate Loaded Transdermal Reservoir Gel Drug Delivery Systems - SreeHarsha, Nagaraja; Hiremath, Jagadeesh G; Rawre, Bimlesh Kumar; Puttaswamy, Niranjan; Al-Dhubiab, Bandar E; Venugopala, Katharigatta N.; Akrawi, Sabah H; Meravanige, Girish; Attimarad, Mahesh; Nair, Anroop B (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Successful treatment of cancer is yet remained as a challenging concern in public health. Transdermal delivery of hormonal therapy offers several advantages over the oral route associated with potential side effects. Methods: The present investigation preparation and screening of rate controlling membranes using Eudragit release liners of RS 100, hydroxyl propyl methyl cellulose K4M (HPMC K4M) and ethyl cellulose by plate casting method and their physicochemical characterization. The prepared release liners were subjected for preformualtion studies (thickness, weight variation, moisture uptake, folding endurance and moisture loss). Tamoxifen citrate is an ideal molecule for the transdermal reservoir for the preparation of gel dosage form due its dosage regimen. Results: The main investigation, topical gel TC was prepared using HPMC K4M and Carbopol 934 as gelling agents in different proportions with Dimethyl Sulfoxide (DMSO) as a penetration enhancer. TC gels were subjected for the physicochemical parameters such as pH, viscosity, spreadability. Conclusion: The TC gel diffusion was conducted by using rate controlling membranes (release liner). The TC gel skin permeation was investigated by using excised rat skin as a barrier.
Keywords: Transdermal reservoir; Gel; Tamoxifen Citrate (TC); Penetration Enhancer